Estimación econométrica de una función -.... de demanda de crédito para el Ecuador: período enero 1990 — diciembre 1997 - Veintimilla Lozano, Eduardo (2000)
This paper studies the Ecuadorian financial system”s credit demand behavior and the variables that determine it, during the period January 1990 - December 1997, with an annual prediction for 1998. Starting from a theoretical basis, we used an econometric model of cointegration for the structuring of the total credit demand function, at the same time, we present three equations to measure the behavior of the institutional demand by loan category (consumption, guaranteed, mortgage). GDP, the cxchange rate and the intercst rate arc the most important variables in the determination of the credit demand, with different level of confidence in the sectorial quantification of credit by type. Moreover, we study the causal relationship between the different variables that enter in the equations, using the Granger Method for its statistical estimation. The study include the analysis of credit demand evolution, explaining their annual cyclical variations and the effects caused by the recessive periods, discovering the structural nature of this part of the economy.